Males of Nectarinella Bequaert (Hymenoptera, Vespidae, Polistinae) - James M. Carpenter; Sidnei Mateus (Revista Brasileira de Entomologia, 2004)
The males of both species of the paper wasp genus Nectarinella Bequaert, N. xavantinensis Mateus & Noll and N. championi (Dover), are described, and the genitalia illustrated. These are compared to species in the closely related genera Chartergellus, Leipomeles, Marimbonda, Parachartergus and Pseudopolybia. Os machos das duas espécies de vespas sociais do gênero Nectarinella Bequaert, N. xavantinensis Mateus & Noll e N. championi (Dover), são descritos e suas genitálias ilustradas. São feitas comparações com espécies de gêneros estreitamente relacionados, Chartergellus, Leipomeles, Marimbonda, Parachartergus e Pseudopolybia.